A morphological study comparing heart size measurement on chest radiograph with echocardiography in local population - Ahmed Ali Khan; Aisha Qamar (Journal of the Pakistan Medical Association, 2023)
Objectives: To investigate heart size on chest X-ray via cardiothoracic ratio, and to correlate it with echocardiographic measurements. Method: The comparative analytical, cross-sectional study was conducted at the Pakistan Navy Station Shifa Hospital, Karachi, between January 2021 and July 2021. The radiological parameters were measured on chest X-rays posterior-anterior view, and the echocardiographic parameters were measured using 2-dimensional transthoracic echocardiography. The absence or presence of cardiomegaly on both imaging modalities was modelled as a binary categorical variable and compared. Data was analysed using SPSS 23. Results: Of the 79 participants, 44(55.7%) were males and 35(44.3%) were females. The mean age of the sample was 52.71±14.54 years. There were 28(35.44%) enlarged hearts on chest X-ray and 46(58.22%) on echocardiography. The sensitivity and specificity of chest X-ray were 54.35% and 90.90%, respectively. The positive and negative predictive values were 89.28% and 58.82%, respectively. The accuracy of chest X-ray in identifying an enlarged heart was 69.62%. Conclusion: The cardiac silhouette on a chest X-ray could demonstrate heart size through simple measurements with high specificity and reasonable accuracy. However, a normal heart size on chest X-ray may not have a normal function. Key Words: Heart size, Cardiomegaly, Cardiothoracic ratio, Chest X-ray, PA view, Transthoracic echocardiography.